Craniofacial Morphology With Genetic Influence Of Abo Blood Group In Malaysian Orthodontic Patients - FATHIN FADHILAH BINTI AHMAD SHOKOR,; WAN SURIANA WAN AB RAHMAN,; MOHAMMAD KHURSHEED ALAM, (International Journal of Pharma and Bio Sciences, 2015)
The prime purpose of this study was to evaluate the craniofacial morphology with genetic influence of ABO blood group in Malaysian orthodontic patients. A total of 200 orthodontics patients were selected using simple random sampling. The mean age of the population of this study was 18.98±4.14. The blood group of each patient was determined using the tile method. Age, gender, race, and lateral cephalogram were obtained from the patient’s records. Craniofacial morphology (SNA, SNB, ANB, MMA, ALFH, UIA, LIA, ULA, UL-E, LL-E) were digitally analyzed using lateral cephalogram. There were 25.5% of patients from blood group A, 27% of blood group B, 40% of blood group O and 7.5% of blood group AB. The results showed no significant difference between ABO blood group craniofacial morphology. In conclusion, this study has shown that there was no genetic influence of ABO blood group in relation to variation in craniofacial morphology. Hence, the type of malocclusion cannot be predicted in the respective blood group.